2017
DOI: 10.1186/s40729-017-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effectiveness of concentrated growth factor on osseointegration

Abstract: BackgroundGrowth factor-containing products have been reported to increase implant stability and accelerate osseointegration. Concentrated growth factor (CGF) can be used for this purpose with the growth factors it contains. The aim of this study is to assess the effect of CGF on implant stability and osseointegration.MethodsTwelve patients with maxillary anterior toothless were included in the study. Implant cavities prepared in the study group were covered with CGF membrane before implant placement, but conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 33 publications
2
52
0
Order By: Relevance
“…Histomorphometric analysis showed significantly higher mean percentage of new bone formation in group B (treated with CGF) at 66.939%, while mean percentage of new bone formation in group A (control group) was at 25.662% Student's t -test revealed that the difference between both groups was statistically significant (p=0.0001). this indicated accelerated bone formation in group B which comes in agreement with results reported by Honda etal 2013 (7) , Durmuslar etal 2016 (9) , Wang etal 2016 (10) , Pirpir etal 2017 (11) , Talaat etal 2018 ( 13) ; whom all found CGF to promote proliferation of osteoblasts and osteogenic maturation and mineralization which led to accelerated healing around the dental implant and further more implant stability and better surgical defect fill.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Histomorphometric analysis showed significantly higher mean percentage of new bone formation in group B (treated with CGF) at 66.939%, while mean percentage of new bone formation in group A (control group) was at 25.662% Student's t -test revealed that the difference between both groups was statistically significant (p=0.0001). this indicated accelerated bone formation in group B which comes in agreement with results reported by Honda etal 2013 (7) , Durmuslar etal 2016 (9) , Wang etal 2016 (10) , Pirpir etal 2017 (11) , Talaat etal 2018 ( 13) ; whom all found CGF to promote proliferation of osteoblasts and osteogenic maturation and mineralization which led to accelerated healing around the dental implant and further more implant stability and better surgical defect fill.…”
Section: Discussionsupporting
confidence: 87%
“…The authors concluded that the use of CGF method can replace the chondrocyte scaffold approach in cartilage regeneration. 11 Assessed the effect of CGF on implant stability and osseointegration in patients. The authors concluded that CGFs had positive effect on implant stabilization and accelerated osseointegration.…”
Section: Introductionmentioning
confidence: 99%
“…16 As CGF was produced by alternate centrifugation, CGF contains abundant autologous growth factors that can promote cell proliferation, migration, osteogenic differentiation, and angiogenic properties in wound healing and bone regeneration. [17][18][19][20][21][22] Our recent studies revealed that CGF injection in hairless scalp could enhance the hair density and optimize the hairless appearance in AGA patients. 23 Therefore, we expanded on the results of previous studies by combining MXD with CGF and hypothesized that CGF intensifies the MXD efficacy to generate a more beneficial and stable HG effect on AGA.…”
Section: Introductionmentioning
confidence: 99%
“…PRF gained its popularity as a healing biomaterial for both soft and hard tissue because of the presence of various growth factors also it would facilitate tissue healing and regeneration by enhancing angiogenesis, chemotaxis, cell proliferation and differentiation and extracellular matrix synthesis [9,10] . For best outcomes in human tissue healing and regeneration, mutual interaction between a scaffold (fibrin matrix), platelets, growth factors, leukocytes, and stem cells are required [11,12] .…”
Section: Introductionmentioning
confidence: 99%